الوظائف التنفيذية لدى المرضى المصابين بالتصمب المويحي ومرض الباركنسون دراسة ميدانية لست حالات بمدينة الأغواط - فاطمة الزهراء علاوة; ثلجة دومة; سعدية زروق (My University, 2023)
Our current study aims to identify the operational functions of patients with sclerosis and Parkinson's disease. The objectives of this study are based on the following hypotheses: -The level of executive functions in plaque sclerosis and Parkinson's is poor. -There are no differences between the impact of these diseases on executive functions due to the type of injury factor. To verify the hypotheses, we applied the MOCA cognitive assessment test to the study group of 6 cases, drawing on the descriptive approach based on a case study tool, and the following results were achieved: -The level of executive functions in cases of mild sclerosis. -The level of executive functions in Parkinson's sufferers is poor. -There are no differences between the impacts of these two diseases on executive functions for Parkinson's patients. Keywords: Executive functions, Sclerosis, Parkinson's, MOCA cognitive assessment test